Ultrasound-aided pH-shift processing for resource-smart valorization of salmon and herring side streams - Michaela V. Santschi; Ingrid Undeland; Mehdi Abdollahi (Ultrasonics Sonochemistry, 2023)
The possibility of reducing the amount of fresh water used during alkaline the pH-shift processing of salmon head (SH) and herring frame (HF) was evaluated with ultrasound (US) as a tool to mitigate its negative effects on protein yield. The role of water ratio and US for homogenate viscosity, mass yield, crude composition, functional properties and lipid oxidation of the SH and HF protein isolates were also investigated. Applying US during the solubilization step of the pH-shift process completely compensated for the reduced protein yield coming from using 3 rather than 6 volumes of water for HF, but not for SH. Using US had no negative effect on the composition and protein functionality of the HF protein isolate. However, it slightly increased its level of secondary lipid oxidation products. Altogether, applying US during the pH-shift processing at low water ratios can be a promising solution for more resource-smart valorization of herring side streams.